Adults with Down syndrome in randomized clinical trials targeting prevention of Alzheimer's disease. Issue 10 (7th December 2021) - Silverman, Wayne; Krinsky‐McHale, Sharon J.; Zigman, Warren B.; Schupf, Nicole; ,
Abstract: Introduction: Adults with Down syndrome, the largest population genetically predisposed to high risk for Alzheimer's disease (AD), are ideally suited participants for clinical trials targeting prevention. Critically important considerations for the design of such trials include appropriate selection of participants, outcome measures, and duration of follow‐up. Methods: Archived data for 12 measures of performance over a 3‐year period were analyzed for 185 adults with Down syndrome 36 years of age and older with presumptive preclinical AD. Results: Declines over 3 years were not observed prior to 46 years of age. However, declines were observed at older ages, increasing monotonically for groups aged 46‐49, 50‐55, and >55, as did incidence of prodromal AD and dementia. Discussion: Significant decline over a 2‐ to 3‐year period for a prospective placebo group of adults with Down syndrome enrolled in clinical prevention trials can only be expected when inclusion is limited to adults older than 45 years of age.